-12=3+x

Simple and best practice solution for -12=3+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12=3+x equation:


Simplifying
-12 = 3 + x

Solving
-12 = 3 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-12 + -1x = 3 + x + -1x

Combine like terms: x + -1x = 0
-12 + -1x = 3 + 0
-12 + -1x = 3

Add '12' to each side of the equation.
-12 + 12 + -1x = 3 + 12

Combine like terms: -12 + 12 = 0
0 + -1x = 3 + 12
-1x = 3 + 12

Combine like terms: 3 + 12 = 15
-1x = 15

Divide each side by '-1'.
x = -15

Simplifying
x = -15

See similar equations:

| 6(r-5)= | | 2/3n+2=16 | | 1/2(x+1)=16 | | 4x-5=1+6x | | 3z+31=-2z+16 | | -5(n-1)=60 | | 5(3x+1)=2x-7 | | b(b-3)=b+12 | | -2x+6y=20 | | 3xy-2x=y | | 6m+3(2m+5)+7=11m+22 | | -6y-1.7-4.6y+1.3y-4= | | 5a+8x+2=54 | | 2(-3p+5)=-4(p+4) | | 8=4x(r+4) | | 19.5x=52 | | 1/5(x+2)=-16 | | (4b-24)^2/2^3x5 | | 5p+3=-92 | | 7(a+5)-12=3a+6 | | 7(3x+1)=5x-8x | | 11(t-6)+4t=5(3t+2)-9 | | -16x^5-44x^4+30x^3=0 | | -3=x/6-6 | | 9x-(8x+2)=2x-40 | | 12-6x=3x-3 | | 6m+3(2m+5)+7=0 | | 6=n-8 | | -2AH=V^2-U^2 | | 28+3p=-4p | | x-2y^2-8y=3 | | 19x-4=10x-40 |

Equations solver categories